Detecting Gene-Environment Interaction for Maternal Exposures Using Case-Parent Trios Ascertained Through a Case With Non-Syndromic Orofacial Cleft - Zhang, Wanying; Venkataraghavan, Sowmya; Hetmanski, Jacqueline B.; Leslie, Elizabeth J.; Marazita, Mary L.; Feingold, Eleanor; Weinberg, Seth M.; Ruczinski, Ingo; Taub, Margaret A.; Scott, Alan F.; Ray, Debashree; Beaty, Terri H. (Frontiers in Cell and Developmental Biology, 2021)
Two large studies of case-parent trios ascertained through a proband with an orofacial cleft [OFC, which includes cleft lip and palate, cleft lip alone or cleft palate alone] were used to test for possible gene-environment (GxE) interaction between genome-wide markers (both observed and imputed) and self-reported maternal exposure to smoking, alcohol consumption and multi-vitamin supplementation during pregnancy. The parent studies were: GENEVA which included 1,939 case-parent trios recruited largely through treatment centers in Europe, the US and Asia; and 1,443 case-parent trios from the Pittsburgh Orofacial Cleft (POFC) study also ascertained through a proband with an OFC including three major racial/ethnic groups (European, Asian and Latin American). Exposure rates to these environmental risk factors (maternal smoking, alcohol consumption and multivitamin supplementation) varied across studies and among racial/ethnic groups creating substantial differences in power to detect GxE interaction, but the trio design should minimize spurious results due to population stratification. The GENEVA and POFC studies were analyzed separately, and a meta-analysis was conducted across both studies to test for GxE interaction using the 2 df test of gene and GxE interaction and the 1 df test for GxE interaction alone. The 2 df test confirmed effects for several recognized risk genes, suggesting modest GxE effects. This analysis did reveal suggestive evidence for GxVitamin interaction for CASP9 on 1p36 located about 3Mb from PAX7, a recognized risk gene. Several regions gave suggestive evidence of GxE interaction in the 1 df test. For example, for GxSmoking interaction the 1 df test suggested markers in MUSK on 9q31.3 from meta-analysis. Markers near SLCO3A1 also showed suggestive evidence in the 1 df test for GxAlcohol interaction, and rs41117 near RETREG1 (a.k.a. FAM134B) also gave suggestive significance in the meta-analysis of the 1 df test for GxVitamin interaction. While it remains difficult to obtain definitive evidence for GxE interaction in genome-wide studies, perhaps due to small effect sizes of individual genes combined with low exposure rates, this analysis of two large case-parent trio studies argues for considering possible GxE interaction in a comprehensive study of complex and heterogeneous disorders such as OFC.